Body image experiences in retired Olympians: Losing the embodied self - Papathomas, A.; Petrie, T.; Moesch, K.; Newman, H. J. H. (Psychology of Sport and Exercise, 2025)
Athlete body dissatisfaction is prevalent across sports and can lead to disordered eating, negative affect, and poor mental health. Whether body image concerns persist into athletic retirement is a focus of research, predominately involving survey-based data in usually sub-elite athletic samples. This study is the first to focus on the meanings elite athletes ascribe to their bodies in retirement. We recruited 31 retired elite athletes, including 23 former Olympians, to participate in a semi-structured interview. More than 25 h of interview data was transcribed verbatim and subject to a reflexive thematic analysis. We constructed 4 major themes to describe athlete experiences: 1) A legacy of body-conscious culture 2) The struggle for "normal", 3) Loss of body as loss of self, 4) Towards new meanings and identities. Athletes explained how the body surveillance culture of elite sport echoed into their post-sport lives. An Olympian identity was considered an embodied identity, so body changes represented a loss of the self. Adjusting to regular eating and exercise routines was deemed challenging, with minimal access to guidance and support. Accepting the inevitability of physical changes in retirement and finding new meanings and identities, were deemed effective coping strategies. Athletes` insights can support sport psychologists and elite sport organisations to devise strategies and policies to facilitate adaptation to body changes post-retirement from sport.